Recent Progress on Primary Central Nervous System Lymphoma—From Bench to Bedside - Shao, Liang; Xu, Chengshi; Wu, Huijing; Jamal, Muhammad; Pan, Shan; Li, Sirui; Chen, Fei; Yu, Ding; Liu, Kui; Wei, Yongchang (Frontiers in Oncology, 2021)
Primary central nervous system lymphoma (PCNSL) is a rare sub-type of extra-nodal lymphoma. The high relapse rate of PCNSL remains a big challenge to the hematologists, even though patients exhibit exquisite sensitivity to the methotrexate-based chemotherapeutic regimens. Recently, the advent of Bruton's tyrosine kinase inhibitor (BTKi) and CAR T treatment contributes to a proportion of patients’ additional treatment options. However, either BTKi monotherapy alone or in combination with conventional chemotherapy is still a clinical question. Meanwhile, the status of CAR T therapy in PCNSLs needs to be elucidated. In this review, we summarized the latest progress in the epidemiology, pathology, clinical manifestation, diagnosis and treatment options for PCNSLs.